Treatment for Flexible Flatfoot in Children With Subtalar Arthroereisis and Soft Tissue Procedures - Li, Bing; He, Wenbao; Yu, Guangrong; Zhou, Haichao; Xia, Jiang; Zhao, Youguang; Zhu, Hui; Yu, Tao; Yang, Yunfeng (Frontiers in Pediatrics, 2021)
Background: Children with flexible flatfoot is common in clinics and there is no unified conclusion on surgical treatment. And for some patients with severe deformities, the correction of the subtalar joint arthroereisis combine the release of the Achilles tendon or gastrocnemius muscle release is still not satisfactory. The main aim of the present study was to investigate the therapeutic outcomes of subtalar arthroereisis combined with Achilles tendon or gastrocnemius recession and medial soft tissue (spring ligament, talonavicular joint capsule, tibionavicular ligaments and tibiospring ligaments) tightening for treating flexible flatfoot with severe deformities. Methods: Thirty patients (32 feet) with pediatric flexible flatfoot who underwent subtalar arthroereisis and soft tissue procedures during January 2016 to January 2018. There were 18 males (20 feet) and 12 females (12 feet) with an average age of 9.5 years (range, 8–12 years). We used the AOFAS scores and VAS scores combined with angles measure to evaluate the pre-operative and post-operative status. Results: Thirty patients (32 feet) were followed up for 25.3 months on average (range, 18–36 months). There was no infection. Post-operative foot pain, arch collapse, and other symptoms improved. At last follow-up, the Meary angle was decreased from 17.5° ± 4.4° to 4.1° ± 1.2° (P < 0.05), the talar-first metatarsal (AP) was decreased from 15.3° ± 3.1° to 4.8° ± 1.3°(P < 0.05), The mean AOFAS score was rose from 66.6 ± 5.8 to 88.6 ± 7.9 (P < 0.05), the mean VAS score was decreased from 6.6 ± 0.6 to 1.7 ± 0.3 (P < 0.05). Conclusion: The subtalar arthroereisis combined with soft tissue procedures can effectively correct flexible flatfoot in children and it is a significant method for severe forefoot abduction reconstruction. Level of Evidence: IV